Benefits of SMOGRA for Pro-Environmental Behavior at SD Muhammadiyah 24 Surakarta - Rini Kuswati; Kholifah Syafrina Hasna; Muhammad Rakha Kusuma Dewa; M. Ilham Timur Abdillah (Universitas Muhammadiyah Surakarta, 2026)
Environmental awareness in schools plays an important role in supporting sustainable environmental behavior and strengthening the implementation of the Adiwiyata program. SD Muhammadiyah 24 Surakarta is one of the schools that aims to become an environmentally friendly school; however, the school still faces several challenges, including limited environmental awareness among students, inadequate waste management behavior, and the lack of technology utilization in supporting environmental management activities. This community service program aimed to introduce Smart Monitoring Green Action (SMOGRA) and improve pro-environmental behavior among students, teachers, and educational staff at SD Muhammadiyah 24 Surakarta. The methods used in this activity included coordination, environmental socialization, counseling, demonstrations, and interactive discussions. The activities were conducted in several stages, starting from coordination with the school principal, environmental socialization for students, counseling for teachers and staff, and demonstrations of SMOGRA utilization as an Internet of Things (IoT)-based environmental monitoring medium. The results of the activity showed positive responses from participants regarding the implementation of environmentally friendly school culture and the importance of pro-environmental behavior. Students demonstrated enthusiasm during the environmental socialization activities, while teachers and staff showed interest in utilizing technology to support environmental education and school environmental management. The implementation of SMOGRA provided additional understanding regarding the integration of technology and environmental education to support the development of sustainable environmentally friendly school culture.